(untitled) (International Journal of Studies in Nursing, 2019)
Purpose: To show that the concept of “brain death” is a purely utilitarian construct which does not have adequate medical foundation. Methods: Presentation of known and novel arguments from the medical literature and unknown arguments from the philosophical literature. Results: There are multiple self-evident inconsistencies, contradictions and logical errors inherent in the concept of “brain death” according to which this concept is obviously invalid. Conclusion: It is considered unavoidable that the only honest option is the definitive abandonment of the concept of “brain death”.